Towards a methodology for the assessment of culture-derived spatial economic development: The case of visual artists in the United States - Alkistis Dalkavouki (European Journal of Geography)
The discourse of economic development through culture and its applications have increasingly received more attention in geographic academia. However, there has been little insight into how the breakthroughs and paradigms of more successful experiments could be sensitively and carefully used for the benefit of less experienced areas. This paper presents an attempt to rectify this, by proposing the use of tangible data from the United States, a country with extensive experience in cultural development and governance. It presents a piece of that research, in the form of a trial methodology for assessing significant clusters of cultural development and identifying their causes. After briefly overviewing the development of the theory of cultural development and defining some basic terms –artists and their definition for quantitative research, (creative) clusters, and creative cities–, a methodology will be proposed and showcased. It will depend on exploratory spatial analysis and the concept of the “artistic dividend”, a method of more directly measuring artists’ contributions to their local economies by counting their numbers and aggregating their income. Data will be taken from the American Community Survey for its thematic and spatial detail, with visual artists being used as an example category. The decennial evolution of clusters will also be inspected and displayed. Finally, the methodology’s further applications, possible evolutions (use of further literature review and regression methods for discovering factors), and distilled focus (improvements by qualitative methods) will be assessed, for its implementation in the final thesis.